Pengaruh Kepuasan Pelatihan, dan Keterlibatan Kerja Terhadap Niat Berpindah Karyawan (Studi Kasus : PT. XYZ Perusahaan Jasa Konstruksi Swasta) - Yonathan Fernando Daiva; Mukti Rahardjo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
Human resources are an important role in the company's success in achieving its goals. without human resources, the company's goals will certainly not be achieved. employee turnover problems that will certainly be faced by every company. if the number of employee turnovers is high, of course this should be concern to the company so as not to hinder the achievement of company goals.The purpose of this study was to determine the effect of training satisfaction, work involvement and turnover intention at PT. XYZ Private Construction Company. This research was conducted to employees at PT. XYZ. The sampling method uses Purposive Sampling. Data collection was carried out by distributing questionnaires to 59 respondents. And this type of research is quantitative and uses analytical methods with the SmartPLS 3.0 program.The results showed that training satisfaction did not have a negative effect on turnover intention. Training satisfaction has a positive effect on work involvement. Work involvement has a negative influence on turnover intention. and there is a negative influence on job involvement mediating between training satisfaction and turnover intention.